SEX- AND GENDER-RELATED ASPECTS OF PATHOGENESIS AND CLINICAL COURSE OF GENERALIZED PERIODONTITIS - Pompii, О.О.; Pompii, Е.S. (World of Medicine and Biology, 2025)
The literature review presents current perspectives on the impact of sex- and gender-related differences among patients on the pathogenesis and clinical course of generalized periodontitis. The biological factors of the disease are analysed in detail, including hormonal background, genetic predisposition, peculiarities of immune responses, and the oral microbiome in people of different sexes. The paper presents indicators of the prevalence of periodontitis depending on the patients’ behavioural factors, lifestyle, bad habits, and other gender factors. The article discusses the clinical symptoms of inflammatory lesions of periodontal tissues, which differ between men and women. The article outlines the problematic issues of the gender-oriented approach in dentistry that require further scientific research to improve the clinical effectiveness of the treatment of generalized periodontitis and the development of modern methods of individual prevention.
Keywords: generalized periodontitis; sex-related characteristics; gender differences; risk factors; gender-specific medicine